Galhofa: the Portuguese wrestling between tradition and survival (Revista de Artes Marciales Asiáticas, 2022)
This paper aims to present the galhofa, a traditional wrestling style practiced in Portugal, especially in Trás-os-Montes, in the northern region. Part of an oral and folk tradition, galhofa has survived with no systematic organization, either regarding its rules or even its techniques. Thus, this paper is focused on introducing and discussing the galhofa as an activity between tradition and sportization. Data was collected in Bragança in 2019 through interview and immersion activity, along with images and videos from field research conducted in Parada between 1997 and 2001. Both the visit to Bragança and the analytical process were conducted via phenomenology and inspired by esthesiology and emersiology. Overall, the experience of galhofa encompasses a free way of fighting with the main objective of keeping the opponent’s back and shoulders on the floor for a few seconds. It is historically related to a manly activity and it is often associated as a ritual of passage from adolescence to manhood. As the only traditional Portuguese wrestling modality surviving nowadays, the galhofa can be considered as a very unique fighting practice. However, there are some shared aspects with other martial arts and combat sports, especially more traditional ones, such as capoeira, loita or lucha leonesa. Under the risk of disappearing, it faces an ongoing sportization process, which includes a more gender equality agenda and a systematic organization of techniques and competition procedures. Relevant changes have also been made towards making this practice more popular and widely known, such as establishing it as part of the undergraduate curriculum on Sports degree at the Polytechnic Institute of Bragança.